Shared Risk Link Group disjointness and geodiverse routing: A trade‐off between benefit and practical effort - Girão-Silva, Rita (2020)
The resilience to disasters is a very relevant problem in telecommunication networks. This work addresses the problem of 1+1 optical lightpath protection considering maximally shared risk link group (SRLG)-disjoint geodiverse paths, applied in the context of an optical network. The resilience to geographically correlated disasters is accomplished by guaranteeing geodiversity of the paths. This work focuses on estimating the increase of the path lengths and the increase in cost of the required transponders, compared to simple link-disjointness (i.e., when no constraints on SRLG-disjointness or geodiversity are considered). Results in different networks allow to evaluate the effect of SRLG-disjointness to ensure some geodiversity.